2013
DOI: 10.1111/ors.12049
|View full text |Cite
|
Sign up to set email alerts
|

Use of dexamethasone to minimise post‐operative sequelae after third molar surgery: comparison of five different routes of administration

Abstract: Clinical relevanceScientific rationale for study: Many methods have been tried to 'smooth' post-operative period after surgical extraction of impacted third molars, including pharmacological means. Local application of dexamethasone seems to be a simple and effective way. Quality of life measures have recently been included in assessment of surgical outcomes. Principal findings: Clinically significant effects of local and systemic steroid on post-operative sequelae as compared to control. Practical implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Trismus, edema, and pain are normal sequlae of third molar surgery; Therefore CS was used for their anti-inflammatory, and analgesic effects to reduce these consequences. (15,16) The main results of this study supported this suggestion, were the injection of a single dose of 8 mg Dx into Pm, immediately before surgical removal of lower 3 rd molar in SG enabled them to regain IID, prevent edema, and reduce pain in agreement with Boonsiriseth. (14) Dx is an ideal synthetic glucocorticoid drug with biological half-life from 36-54 h, 20-30 times more potent than cortisol, it has no mineralocorticoid activity, it maintains a high therapeutic plasma level through the early postoperative period, and it shows a faster cell membrane penetration.…”
Section: Discussionsupporting
confidence: 71%
“…Trismus, edema, and pain are normal sequlae of third molar surgery; Therefore CS was used for their anti-inflammatory, and analgesic effects to reduce these consequences. (15,16) The main results of this study supported this suggestion, were the injection of a single dose of 8 mg Dx into Pm, immediately before surgical removal of lower 3 rd molar in SG enabled them to regain IID, prevent edema, and reduce pain in agreement with Boonsiriseth. (14) Dx is an ideal synthetic glucocorticoid drug with biological half-life from 36-54 h, 20-30 times more potent than cortisol, it has no mineralocorticoid activity, it maintains a high therapeutic plasma level through the early postoperative period, and it shows a faster cell membrane penetration.…”
Section: Discussionsupporting
confidence: 71%
“…This study introduced the endo-alveolar approach for administrating corticosteroid which has the benefit of easy placement, and providing a localized effect with reduced systemic side effects of corticosteroids. A further study on endo-alveolar application was later performed once and this study confirmed its benefit [ 23 ].…”
Section: Resultsmentioning
confidence: 85%
“…Thereafter, no significant difference between both groups Significantly less in Group A on Day 2 post-operative Antunes et al (2011) [ 29 ] 60 Administered pre-emptive A. Dexamethasone 8 mg/intramuscular (masseter) ( n = 18) B. Dexamethasone 8 mg/oral ( n = 20) C. Control—no medication ( n = 22) Significantly less in dexamethasone groups compared to control on Day 2 for swelling No significant difference between both dexamethasone Significantly less medication consumed for dexamethasone groups compared to control at Day 1 ( P = 0.007) No significant difference between both dexamethasone groups Significantly less in dexamethasone groups compared to control on Day 2 ( P < 0.05) No significant difference between both dexamethasone groups Boonsiriseth et al (2012) [ 30 ] 40 Administered post-operative A. Dexamethasone 8 mg/intramuscular (deltoid) ( n = 20) B. Dexamethasone 8 mg/oral ( n = 20) Both routes were effective, with no significant difference between groups Both routes were effective, with no significant difference between groups Both routes were effective, with no significant difference between groups Klongnoi et al (2012) [ 31 ] 40 Administered pre-emptive A. Dexamethasone 8 mg/intramuscular (deltoid) ( n = 20) B. Control—saline injection ( n = 20) Significantly less swelling in Group A on Day 2 Significantly less pain in Group A on Day 2 and Day 7 There was no significant difference between both groups Bortoluzzi et al (2013) [ 32 ] 50 Administered pre-emptive A. Dexamethasone 8 mg + amoxicillin 2 g/oral ( n = 12) B. Placebo 8 mg + amoxicillin 2 g/oral ( n = 12) C. Dexamethasone 8 mg + placebo 2 g/oral ( n = 14) D. Control—placebo 8 mg + placebo 2 g/oral ( n = 12) No significant difference between all groups No significant difference between all groups No significant difference between all groups Majid and Mahmood (2013) [ …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, none of these studies compared the effects of these 2 corticosteroids given as a submucosal injection, which has been shown to be as effective as those administered via the intramuscular route. [16][17][18][19][20] Therefore, we performed this study to compare these corticosteroids, administered as a single preoperative dose, using a dosage chosen based on the information on the minimum effective dose reported by previous studies. reported comprehensively by Ngeow and Lim, 2 and readers are referred to this publication for concise information.…”
Section: Discussionmentioning
confidence: 99%